Simulations of nanocomposite carbon films - Kelires, Pantelis C. (My University, 2007)
The structure, stability, and mechanical properties of composite carbon films containing nanodiamonds and nanotubes are investigated by means of Monte Carlo and Tight-binding Molecular Dynamics simulations. The nanodiamonds are found to be stable in dense tetrahedral amorphous carbon matrices. The resulting composite materials have significantly enhanced elastic moduli compared to the pure amorphous phase, approaching the moduli of diamond. They are superhard, with a high ideal strength. The simulations also shed light into the fracture mechanisms of the material. It is found that fracture in the nanocomposites, under tensile or shear load, occurs inter-grain. For nanotube composites, it is shown that van der Waals forces play a vital role in shaping up the interfacial geometry, producing a curved graphitic wall surrounding the tubes, without covalent bonding between the tube and the matrix. The most stable structures are predicted to have intermediate densities, high anisotropies, and increased elastic moduli compared to pure amorphous carbon films.
Keywords: Anisotropy; Computer simulation; Covalent bonds; Density (specific gravity); Diamonds; Elastic moduli; Hardness; Molecular dynamics; Monte Carlo methods; Nanocomposites; Van der Waals forces